2019
DOI: 10.1186/s12974-019-1525-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment response in adults with relapsing MOG-Ab-associated disease

Abstract: Background Myelin oligodendrocyte glycoprotein antibodies (MOG-Ab) are related to several acquired demyelinating syndromes in adults, but the therapeutic approach is currently unclear. We aimed to describe the response to different therapeutic strategies in adult patients with relapsing MOG-Ab-associated disease. Methods This is a retrospective study conducted in France and Spain including 125 relapsing MOG-Ab patients aged ≥ 18 years. First, we performed a survival ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 43 publications
5
151
0
6
Order By: Relevance
“…There are individuals who fulfill criteria for MS, but are often atypical; perhaps the MOG-IgG result has utility in this context in ruling out MS, and should not be ignored out of hand. Importantly, when extrapolating from experiences on the treatment of NMOSD and a recent larger study on treatment of patients with MOG-IgG from France, disease modifying treatments for MS may not work in MOG-IgG positive patients and may even exacerbate disease 1,[32][33][34] . The third interpretation is that these low positive results that are not reproducible between centers are not useful clinically and in fact dilute the utility of a more specific test.…”
Section: Iggmentioning
confidence: 99%
“…There are individuals who fulfill criteria for MS, but are often atypical; perhaps the MOG-IgG result has utility in this context in ruling out MS, and should not be ignored out of hand. Importantly, when extrapolating from experiences on the treatment of NMOSD and a recent larger study on treatment of patients with MOG-IgG from France, disease modifying treatments for MS may not work in MOG-IgG positive patients and may even exacerbate disease 1,[32][33][34] . The third interpretation is that these low positive results that are not reproducible between centers are not useful clinically and in fact dilute the utility of a more specific test.…”
Section: Iggmentioning
confidence: 99%
“…MOG Ab-associated disorders encompass a disease entity involving the brain, optic nerve, and spinal cord that is distinct from multiple sclerosis (MS) and aquaporin-4 Ab-positive neuromyelitis optica spectrum disorder (NMOSD) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The reemergence of MOG Ab in the field of autoimmune diagnostics has sparked wide interest, and with ongoing advances in our understanding of MOG Ab-associated disease, requests for MOG Ab testing have risen dramatically, as treatment regimens and prognosis for MOG Ab-positive patients are divergent from MS and aquaporin-4 Ab-positive NMOSD patients (11,16,17). Moreover, some MOG Ab-positive patients, particularly those with relapsing disease or delayed immunotherapy, may accrue residual disability (11,12,(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The reemergence of MOG Ab in the field of autoimmune diagnostics has sparked wide interest, and with ongoing advances in our understanding of MOG Ab-associated disease, requests for MOG Ab testing have risen dramatically, as treatment regimens and prognosis for MOG Ab-positive patients are divergent from MS and aquaporin-4 Ab-positive NMOSD patients (11,16,17). Moreover, some MOG Ab-positive patients, particularly those with relapsing disease or delayed immunotherapy, may accrue residual disability (11,12,(15)(16)(17)(18)(19). As such, early and accurate identification of MOG Ab-seropositivity is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 197 adults with MOG-Ab observed that titres were higher at relapse than in remission. 4 In a large paediatric study, high MOG-Ab titres (≥1:1280) predicted a recurrent non-multiple sclerosis course with 46% sensitivity and 86% specificity. 5 Overall, patients may remain seropositive for years, despite having a monophasic disease.…”
mentioning
confidence: 95%
“…The utility of MOG‐Ab in making treatment decisions remains an area of active debate. A study of 197 adults with MOG‐Ab observed that titres were higher at relapse than in remission . In a large paediatric study, high MOG‐Ab titres (≥1:1280) predicted a recurrent non‐multiple sclerosis course with 46% sensitivity and 86% specificity .…”
mentioning
confidence: 99%